Elaboración e implementación de una guía visual lectora que genere la comprensión lectora en los niños y niñas de 2 a 5 años de edad, para la sala de estimulación temprana de la carrera de educación parvulario de la universidad técnica de Cotopaxi ubicada en la parroquia Eloy Alfaro de la ciudad de Latacunga, provincia de Cotopaxi durante el año 2011-2012 - Toapanta Toctaguano, Paola Janneth (2013)
The present investigative work has taken in order to analyze about the influences of visual reading in a previous knowledge in the children from 2 to 5 years old generating the reading comprehension throw picture, this allowed sorts of abilities to the early encouragement to the students which allow the learning level. The present studies pretended generate a reading visual guide which has a lot of ludic activities with the unique purpose to encourage and reinforce reading comprehension abilities relating their knowledge into the social camp which has been part in a principal instrument into the university however the students add a learning room which help them to increase and improve their knowledge in the visual reading. The present investigative work has been taken throw the camp investigation in the functional appliances picking up techniques which are the surveys to teachers and observation technique in order to create new activities which fall asleep the learning in the students. Has been analyzes and interpreted the results getting the diagnostic which get into that the cotopaxi technical university, teachers, students and specially the parvularia major requires a reading visual with sort of activities and exercises.